2011
DOI: 10.1007/s13361-011-0253-2
|View full text |Cite
|
Sign up to set email alerts
|

Super-Atmospheric Pressure Electrospray Ion Source: Applied to Aqueous Solution

Abstract: This is a follow-up paper of our previous report on an ion source, which was operated at an operating pressure higher than the atmospheric pressure. Besides having more working gas for desolvation, the reduction of mean free path of electrons in a higher pressure environment increases the threshold voltage for gaseous breakdown, thus enabling a stable electrospray for the sample solution with high surface tension without the occurrence of electric discharge. In our previous work, the ion source was not coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…11a, the protein solvent is 2 v/v% formic acid aqueous solution which has recently become a standard reagent for the chemical digestion. Except for the peptide fragment [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], all other hydrolysis products are due to the cleavage at the Asp sites. Comparison was also done with acetic acids (Fig.…”
Section: Rapid In-situ Protein Digestion Ms With Superheated Esimentioning
confidence: 99%
See 1 more Smart Citation
“…11a, the protein solvent is 2 v/v% formic acid aqueous solution which has recently become a standard reagent for the chemical digestion. Except for the peptide fragment [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], all other hydrolysis products are due to the cleavage at the Asp sites. Comparison was also done with acetic acids (Fig.…”
Section: Rapid In-situ Protein Digestion Ms With Superheated Esimentioning
confidence: 99%
“…We have implemented the super-atmospheric pressure ionization MS with pure electrospray, [12][13][14][15][16] corona discharge based chemical ionization, 17) and eld desorption, 18) and had routinely run our mass spectrometer with ion source pressures ranging from several to several tens of atm. For typical analytical application where the solvent composition can be ne-tuned to best-suit the API-ESI, it is unnecessary to pressurize the ion source, though it is possible to get some signal enhancement due to higher gas throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have introduced a series of high pressure ion sources implemented with electrospray, 18,19) nano and probe electrospray, [20][21][22] corona discharge chemical ionization, 23) and eld desorption. 24) ese ion sources were pressurized with air or nitrogen to a pressure higher than atmospheric pressure (p>1 atm), and were connected to API mass spectrometer via various coupling strategies.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the use of pure water as solvent could be advantageous to produce very clean mass spectrum without the interference from hydrophobic contaminants dissolved in organic solvents. 19) Under super-atmospheric pressure and using water as solvent, nanoESI with a solution ow rate of ∼10 nL/min, could also be achieved using plastic pipette tips with inner diameter of ∼100 µm, which was much larger than those of standard nanoESI emitter (1-10 µm). 22) e mass spectrometer, which is designed to work with ESI and other atmospheric pressure ionization (API) source is usually referred as API mass spectrometer (API-MS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation